math

A=1/2h (b1 + b2)

Solve for b1


A=1/2h (b1 + b2)

Solve for b1

I assume this is A = (1/2)(h)(b1 + b2); i.e., the h is in the numerator and not the denominator
Multiply both sides by 2.
2A = (2*1/2)h(b1 + b2).
2*1/2 on the right side is 1.
2A = h(b1 + b2)

expand the right side.
2A = hb1 + hb2.

Subtract hb2 from both sides.
2A - hb2 = hb1 + hb2 - hb2.
The hb2 terms on the right "cancel" or add out.
2A - hb2 = hb1

Divide both sides by h, leaving just b1 on the right side.
[(2A - hb2)/h] = (hb1/h) = b1

I hope this helps. Check my work.


If I divide everything by 2 at the end. Where does the A go.

Would it be Ab2/h = b1

Im kind of lost


Why do you wish to divide everything by 2 from the last step? That will give you 1/2*b1 on the right and you wanted to solve for b1, not 1/2 b1.
Just remember that you can do anything to the equation to get it in the form you wish but whatever you do to one side you must do to the other side. If you are still lost, post what step you don't understand and tell us exactly the problem you are having in taking the next step.


thank you for the help.

is the equation if you were solving for B2
[(2A-hb2)/h]=(hb2/h)=b2 ?????


So what's the answr in the end??

  1. 👍 0
  2. 👎 0
  3. 👁 262
asked by ryan
  1. what if i was solving for h? what would i do?

    1. 👍 0
    2. 👎 0
    posted by dj
  2. A=1/2h(b1+b2) Solve for h

    1. 👍 0
    2. 👎 0
    posted by Kari
  3. Solve for b2: A=1/2h(b1+b2)

    1. 👍 0
    2. 👎 0
    posted by Steven

Respond to this Question

First Name

Your Response

Similar Questions

  1. Calculus

    How do you us implicit differentiation to solve x( y + 2 )^5 = 8 x( y + 2 )^5 = 8 ( y + 2 )^5 d/dx (x) + x d/dx(y+2)^5=d/dx 8 (y+2)^5 + 5x(y+2)^4 dy/dx=0 solve for dx/dy (Broken Link Removed) I assume you want dy/dx. Differentiate

    asked by Patti on April 10, 2007
  2. Math

    We have an important chemsitry test due and I want to make sure that I do not mess up on my algebra. I am dealing with the integrated rate law, but my question is purely algebraically in nature. I hope, somebody can help me. 1)

    asked by Yasemine on May 13, 2013
  3. math

    actually, in a addition to the question i posted a few minutes ago, can someone please help me with a few actual specific questions? thanks so much i'm very confused and i've been working on these all day. *Literal Equations*

    asked by kim on October 26, 2007
  4. algebra

    solve the formula for the given letter. Assume all variables represent non-negative numbers. E=jc^2 solve for c

    asked by sam on July 11, 2010
  5. algebra

    Solve the indicated variable: 1. Volume of a cone: solve for h: V=¨ir^2h/3 2. Temperature formula: solve for C: F=9/5C+32 pleaseeeee help me solve these! plzzz! i have nooo idea how to do these. THANKS! =)))

    asked by kitty kat on September 20, 2009
  6. bobpursly,.math

    Ok, assume it equals zero. 2x + 3y -6=0 subtract 3y from each side. add six to each side. divide both sides by two. its how its in the book i'm suppost to solve for x. but how? How do I solve for the following: Directions solve

    asked by bobpursley on December 19, 2006
  7. Alebra

    Solve 5m - 8 > 12 Solve 12 - 3a > 18 Solve 5m - 4 < 2m + 11 Solve 2r - 18 ≤ 5r + 3 Solve 26p - 20 > 14p + 64 Can someone give me an example to one of these? I don't know how to do these.

    asked by Jessi on December 19, 2016
  8. algebra

    x+1 -x+2 = x+3 ____ _____ ____ 2 3 4 How do I solve this equations? These are fractions mi don't know I'm going to assume your problem is this: (x+1)/2 - (x+2)/3 = (x+3)/4 ...and you are trying to solve for x. If so, here's how

    asked by deborah on February 5, 2007
  9. math444

    x^2/x+3 - 5/x+3=0 *Please solve the rational equation Your non use of parenthesis is annoying and most confusing. I assume you meant x^2/(x+3) - 5/(x+3)=0 multiply both sides of the equation by x+3, and solve.

    asked by margie on March 4, 2007
  10. Substitution Method-Plz help

    Use the Substitution method to solve the system of equations. x + y = -4 x - y = 2 solve for x in the second equation. x= y+2 Put that in for x in the first equation: x+y=-4 (y+2) + y = -4 solve for y. Then, x= y+2 i don't get

    asked by Svetlana on October 17, 2006
  11. Intermediate Algebra

    Combine like terms: -3x^2+2x-4x^2-9+6x-2x^2+8 Solve for x: 8x-11= -11x+18 Solve for x: -2(x-5)+7=z-8-5x Solve for x: (x-2)/5 - 3/2= (x+1)/10 Translate to an algebra statement; do not solve: Seven times the difference of six and a

    asked by Dawn on September 29, 2007

More Similar Questions